Pengaruh Struktur Modal dan Perputaran Modal Kerja Terhadap Profitabilitas pada Perusahaan Sektor Transportasi yang Terdaftar di Bursa Efek Indonesia Periode 2014-2024 - Hasan, Rimah; Sawukir, Sawukir (Jurnal Akuntansi Bisnis dan Ekonomi (JABE), 2026)
This study focuses on examining the effect of capital structure and working capital turnover on profitability in transportation sector companies listed on the Indonesia Stock Exchange (IDX) during the 2014–2024 period. Capital structure is proxied by Debt to Equity Ratio (DER), working capital turnover is proxied through Working Capital Turnover (WCTO), and profitability is calculated using Return On Equity (ROE). This research uses a quantitative approach that utilizes secondary data in the form of company financial reports. Research data was obtained through the Indonesia Stock Exchange website and the websites of various companies that serve as research samples. The population used consists of 18 companies listed on the Indonesia Stock Exchange (IDX) in the transportation industry, a purposive sampling method was used to take samples from 3 selected companies. Data analysis was carried out by panel data regression using EViews 12 software. Based on the results of the study, capital structure partially affects profitability negatively and significantly, Conversely, profitability is not significantly affected by working capital turnover. Simultaneously, capital structure and working capital turnover are proven to have a significant influence on the level of company profitability.